AVALIAÇÃO DA APRENDIZAGEM NA EDUCAÇÃO INFANTIL E OS CONTEXTOS DE VIDA DE CRIANÇAS EMPOBRECIDAS NA CIDADE DE VITÓRIA-ES - Matiazzi, Shellen de Lima (2020)
The research aims to understand the historical and social constitution of poverty and how this phenomenon reverberates in school spaces, emphasizing the educational- evaluative practices developed since childhood and fostering dialogues in a formative con